2010
DOI: 10.1111/j.1365-246x.2010.04548.x
|View full text |Cite
|
Sign up to set email alerts
|

Thickness of the central and eastern European lithosphere as seen bySreceiver functions

Abstract: SUMMARY S receiver functions obtained from seismograms of teleseismic events recorded at 78 European permanent broad‐band stations are used to estimate the thickness of the European lithosphere. Our results provide new, independent information about the lithospheric thickness beneath the Precambrian platform of Eastern Europe and the Phanerozoic platform of central Europe. Detailed high‐resolution images of the lithosphere–asthenosphere boundary (LAB) reveal indications for a typical continental lithosphere o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
85
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 56 publications
19
85
3
Order By: Relevance
“…Koulakov et al (2009) observed the positive P wave velocity anomaly beneath the EEC down to at least 300 km, which indicates even thicker lithosphere compared to . Legendre et al (2012) find no indications of a deep cratonic root below about 330 km for the EEC, while Geissler et al (2010) do not observe any clear indications of deep seismic LAB beneath the EEC either.…”
Section: Review Of Previous Studiesmentioning
confidence: 87%
“…Koulakov et al (2009) observed the positive P wave velocity anomaly beneath the EEC down to at least 300 km, which indicates even thicker lithosphere compared to . Legendre et al (2012) find no indications of a deep cratonic root below about 330 km for the EEC, while Geissler et al (2010) do not observe any clear indications of deep seismic LAB beneath the EEC either.…”
Section: Review Of Previous Studiesmentioning
confidence: 87%
“…The edge of the EEC in Poland, the Teisseyre-Tornquist Zone (TTZ), continues in SW Scandinavia as the Sorgenfrei-Tornquist Zone (STZ). This boundary between Baltica and Phanerozoic Europe is well visible in the basement, Moho depth, as well as in lithospheric thickness (e.g., Lassen and Thybo 2012;ScheckWenderoth and Maystrenko 2013;Grad et al 2009Grad et al , 2014Knapmeyer-Endrun et al 2014;Wilde-Piórko et al 2010;Puziewicz et al 2006;Gregersen et al 2002;Geissler et al 2010). The gravity modeling suggests a very small density value in the uppermost mantle 3.11 g/cm 3 below the younger area of WEP, while for the older area of EEC, it is 3.3 g/cm 3 (e.g., Krysiński et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a seismologically derived LithosphereAsthenosphere Boundary (Fig. 5) has been implemented integrating results of Tesauro (2009), Geissler et al (2010, Karousova et al (2013), Seiberlich et al (2013) and Bianchi et al (2014). The LAB is deepest (up to 150 km bsl) below the Alps, moderately deep (~130 km bsl) below the Bohemian Massif and the Molasse Basin and rises below the Eifel plume (~80 km bsl) in the northwest.…”
Section: The Lithospheric-scale 3d Structural Modelmentioning
confidence: 99%